Enabling monodisperse perovskite phase with buried interface modification toward efficient light-emitting diodes - Jiang, Maowei; Zhang, Xiaomeng; Wang, Feijiu (Nano Research Energy, 2023)
The performance of perovskite light-emitting diodes (PeLEDs) has been drastically improved recently. Therein, the coexistence of polydisperse perovskite domains has been one worthy subject of study. The crystallization of perovskite is affected by the buried interface character with the bottom contact layer; and the trap states also inherently exist at the buried interface of the perovskite film, which induce the nonradiative recombination and impede the PeLED performance. In this work, we focus on the crystallization modulation of monodisperse perovskite nanodomains toward high-performance PeLEDs. We show that a LiBr pre-modification layer on the bottom substrate induces the formation of monodisperse perovskite phase. In this system, the carrier transferring process deriving from the polydisperse phases is reduced. In addition, the LiBr pre-modification layer at the buried interface minimizes the trap states and enhances the radiative recombination of perovskites. Accordingly, our PeLEDs show a champion external quantum efficiency (EQE) of 25.5% for 4 mm2 device, and 22.9% for 100 mm2 device.